STRATEGIES FOR IMPLEMENTING LOCAL CONTENT REGULATIONS IN FIBER OPTIC CABLE MANUFACTURE: A CASE STUDY OF PT ZTT INDONESIA - Zhao Haiwei; Noorhan Firdaus Pambudi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Local Content Requirement (LCR) policies are widely implemented to strengthen domestic industries, enhance value added, and support national economic development. In Indonesia, the mandatory minimum 40% LCR significantly affects strategic sectors, including the fiber optic cable industry, which plays a crucial role in national digital infrastructure. However, structural challenges persist, particularly the dependence on imported raw materials and the limited competitiveness of domestic suppliers. This study aims to analyze the benefits of LCR implementation, identify key challenges faced by PT ZTT Indonesia, and formulate strategic solutions to improve LCR compliance. This research adopts a qualitative case study approach using primary and secondary data, including interviews, observations, and company reports, analyzed through Fishbone and PDSA frameworks. The findings indicate that LCR implementation enhances access to government procurement, strengthens competitiveness, and fosters backward industrial linkages with local suppliers. However, major constraints include limited availability and quality of domestic raw materials, higher production costs, regulatory complexity, technological limitations, and logistical challenges. These factors create operational inefficiencies and hinder optimal LCR achievement. To address these challenges, strategic improvements are proposed, including supplier capacity development, technology upgrading, process optimization, and increased investment in research and development. Strengthening collaboration between industry, government, and suppliers is also essential to improve ecosystem readiness. In conclusion, effective LCR implementation requires an integrated and adaptive approach that aligns policy frameworks with industrial capabilities. Future policies should emphasize flexibility, innovation, and sustainable industrial development to ensure long-term competitiveness and reduced dependency on imports